Education counteracts the genetic risk of Alzheimer’s disease without an interaction effect - Li, Xuping; Zhang, Yushi; Zhang, Chengcheng; Zheng, Ying; Liu, Ruilin; Xiao, Shuiyuan (Frontiers in Public Health, 2023)
Background: Alzheimer's disease (AD) is a major cause of disability and mortality in older adults. This study aimed to investigate the association of AD with education and genetic factors.We conducted a prospective cohort study using data from the UK Biobank.Genetic risk was assessed using a polygenic risk score for AD. The educational level was categorized as either low, intermediate, or high. AD was defined using the International Classification of Diseases and Related Health Problems, 10 th revision.Logistic regression models were used to investigate the independent and combined effects of genetic factors and educational levels on the risk of AD.We included 318,535 participants in this study (age: 56.53 ± 8.09 years; male: 44.81%). Compared with a low genetic risk, a high genetic risk was associated with a significantly greater risk of AD (OR = 7.09, 95% CI: 6.09-8.26). A high educational level was associated with a 30% lower risk of AD compared with a low educational level (OR = 0.70, 95% CI: 0.60-0.81). Combining genetic risk and education categories, individuals with a low genetic risk and high educational level had a more than 90% (OR = 0.09, 95% CI: 0.05-0.16) lower risk of AD compared to those with a high genetic risk and low educational level. There was no significant interaction between genetic risk and educational level regarding AD risk (P for interaction = 0.359).Education counteracts the genetic risk of AD, without an interaction effect. Increasing education to reduce the incidence of AD is of same importance across individuals with different genetic risk. High 0.51% (213/12012) 0.70 (0.60, 0.81) 0.71 (0.61, 0.83) 0.70 (0.60, 0.81)